Environmental protection as market pathology?: carbon trading and the dialectics of the 'double movement' - Carton, Wim (Environment & Planning D: Society & Space, 2014)
Polanyi's concept of the 'double movement' is frequently interpreted as the opposition between the problematic and unsustainable dynamics of the market and the benign and normatively desirable reaction against this by 'society'. This paper questions this dualistic interpretation of the double movement and undertakes a problematization of the Polanyian idea of social and environmental protection. It does this by revisiting the concept of the double movement in light of the recent proliferation of market-based mechanisms for environmental regulation. Through an exploration of the different interpretations of Polanyi's work, the paper presents a dialectical reading of the double movement that conceptualizes the idea of social protection within a broader capitalist framework. This is then illustrated with the case of emissions trading as a particular form of environmental protection. Carbon trading as a mitigation strategy, it is argued, corresponds to the Polanyian idea of 'social protection' in that its protective potential to reduce emissions is itself constrained by the socioeconomic framework within which it operates. This in turn points to the need for a critique of climate mitigation efforts that goes beyond a focus on current problems with emissions trading schemes.
Keywords: EU Emissions Trading Scheme; carbon offsetting; climate change; countermovement; emissions trading; environmental protection; pathology; socioeconomics

Spatial egalitarianism as a social ‘counter-movement’: on socio-economic reforms in Chongqing - Lim, Kean Fan (Economy & Society, 2014)
Through a framework drawn from Karl Polanyi's substantivist theorization of economic practices, this paper evaluates the quest for equitable urbanization in Chongqing, a major city-region in south-western China. Illuminating the tensions arising from two interrelated reforms, namely the ambitious attempt to construct 40 million m2of public rental housing between 2010 and 2012, and the large-scale drive to ensure peasant migrants enjoy equal access to social benefits as current urban residents, the paper explains how the quest for equitable urbanization magnifies two nationwide dimensions of institutionalized uneven development, namely (i) the caste-like categorization of populations according to ‘urban’ and ‘rural’; and (ii) the coastal bias in national economic development. The paper concludes that this state-driven pursuit of spatial egalitarianism in Chongqing expresses the dialecticism of economic development in China: it is a social ‘counter-movement’ against the effects of an uneven spatiality that was instituted to drive and deepen the marketization of Chinese society.
Keywords: China; Chongqing; double movement; economic reform; equality; hukou; public welfare; social change; spatial egalitarianism; state–market relations; substantivist; urban–rural integration

White Knights from the Gulf: Sovereign Wealth Fund Investment and the Evolution of German Industrial Finance - Haberly, Daniel (Economic Geography, 2014)
The period leading up to and following the global financial crisis has been characterized by rising global financial diversity and multipolarity, a process underscored by the growth of so-called sovereign wealth funds (SWFs). To date there has not been any systematic examination of the interactions between this rising global financial diversity and national economic institutional diversity. Here I apply an institutional 'comparative capitalisms' perspective to the analysis of Gulf Cooperation Council ( GCC) SWF investment in German industry since the onset of the global financial crisis. The evidence demonstrates that a growing number of German industrial firms-particularly the major automotive firms at the heart of German industry-have recruited long-term GCC SWF investment as an adaptive response to the stresses of financial restructuring, most importantly the appearance of hostile takeovers as a feature of the German corporate governance landscape. These patterns lend partial support to 'varieties of capitalism' ( VOC) arguments that institutional complementarity and comparative institutional advantage are likely to produce path dependent trajectories of national institutional evolution. They also lend partial support to critiques of VOC, emphasizing, on the one hand, the importance of the Polanyian 'double movement' of market expansion and containment and, on the other, the transnational foundations of national institutional diversity. I conclude that to fully explain these patterns, both VOC theories of institutional complementarity and comparative advantage, and Polanyian theories of the double movement, must be grounded in a 'generalized Darwinian' analysis of population-level selection dynamics.
Keywords: Germany; Gulf Cooperation Council; Polanyian double movement; capitalism; economic geography; financial globalization; foreign investments; generalized Darwinism; industries; liberalization (finance); sovereign wealth funds; variegated capitalism; varieties of capitalism

Urban poverty and regulation, new spaces and old: Japan and the US in comparison - Mahito Hayashi (Environment & Planning A, 2014)
After the 1970s the new urban poverty (NUP) ballooned in Japan and the US, and it evoked policy responses that produced new, rescaled regulatory spaces to contain the poor on the fringe of social rights and the capital circuit. The paper illuminates this process through the comparison of Japanese and US trajectories, both of which, evolving through economic crises, have established unique pathways. The author first constructs a theoretical framework based on Marxian, Polanyian, and Lefebvrean traditions. Then, he compares national-scale poverty regulation in Japan and the US from the 1950s through the 2000s. Lastly, the author examines how the countries' regulation of a major aspect of the NUP--homelessness--intensified multiscalar reseating processes. The paper concludes that regulation of the NUP represents a significant instance of uneven spatial development of capitalism mediated by the state that requires synthetic research.
Keywords: Japan; United States; capitalism; comparative studies; economic development; financial crises; financial crisis; ghettoization; homelessness; rescaling; the capital circuit; the new urban poverty; the regulation approach; uneven spatial development; urban poor

Marketisation, public services and the city: the potential for Polanyian counter movements - Warner, Mildred E.; Clifton, Judith (Cambridge Journal of Regions, Economy and Society, 2014)
Marketisation of urban service delivery gained renewed intensity in the crisis. Mobilising Polanyi’s concept of double movement, we analyse how marketisation of public services both creates and constrains the potential for urban counter movements in the USA and Europe. We identify three main urban responses: ‘hollowing out’, where cities engage in service cut backs; ‘riding the wave’, where cities attempt to harness the market; and ‘push backs’, where cities and citizen movements oppose marketisation. Although the city is constrained by marketisation at national and international levels, we find evidence of push back and, in it, the potential for public service alternatives.
Keywords: city; crisis; double movement; marketisation; public services; urban studies

Radical, reformist, and garden-variety neoliberal: coming to terms with urban agriculture's contradictions - McClintock, Nathan (Local Environment, 2014)
For many activists and scholars, urban agriculture in the Global North has become synonymous with sustainable food systems, standing in opposition to the dominant industrial agri-food system. At the same time, critical social scientists increasingly argue that urban agriculture programmes, by filling the void left by the “rolling back” of the social safety net, underwrite neoliberalisation. I argue that such contradictions are central to urban agriculture. Drawing on existing literature and fieldwork in Oakland, CA, I explain how urban agriculture arises from a protective counter-movement, while at the same time entrenching the neoliberal organisation of contemporary urban political economies through its entanglement with multiple processes of neoliberalisation. By focusing on one function or the other, however, rather than understanding such contradictions as internal and inherent, we risk undermining urban agriculture's transformative potential. Coming to terms with its internal contradictions can help activists, policy-makers and practitioners better position urban agriculture within coordinated efforts for structural change, one of many means to an end rather than an end unto itself.
Keywords: United States; agricultural sociology; alternative food networks; community gardens; food production; food security; neoliberalism; urban agriculture; urban farming; urban studies